A Battery Method to Enhance the Degradation of Iron Stent and Regulating the Effect on Living Cells. Issue 7 (10th June 2022) - Yu, Changchun; Liu, Xiao; Zhang, Jiahao; Chao, Yunfeng; Jia, Xiaoteng; Wang, Caiyun; Wallace, Gordon G.
Abstract: Iron is a promising material for cardiovascular stent applications, however, the low biodegradation rate presents a challenge. Here, a dynamic method to improve the degradation rate of iron and simultaneously deliver electrical energy that could potentially inhibit cell proliferation on the device is reported. It is realized by pairing iron with a biocompatible hydrogel cathode in a cell culture media‐based electrolyte forming an iron‐air battery. This system does not show cytotoxicity to human adipose‐stem cells over a period of 21 days but inhibits cell proliferation. The combination of enhanced iron degradation and inhibited cell proliferation by this dynamic method suggests it might be an approach for restenosis inhibition of biodegradable stents. Abstract : A dynamic method is developed to improve the degradation rate of Fe stents while simultaneously inhibiting cell proliferation and providing energy as a bioelectric power source. It might be an approach useful for inhibition of restenosis with biodegradable Fe stents.